The Effect of Open Ended Approaches and Learning Motivation on Mathematical Learning Outcomes in Class V - Ilki Wahyudi; Sufyarma Marsyidin (International Journal of Educational Dynamics, 2019)
This study aims to reveal the effect of the Open Ended Approach and motivation to learn on the mathematics learning outcomes of fifth grade students in Elementary School. The type of research used is Quasi Experiment with the design of Randomized Control Group Only Design. The population in this study are all elementary school students who have used the 2013 curriculum in Cluster VI Palembayan District registered in the first semester of the 2018/2019 school year with a sample of VB SDN 27 Tapian Kandis as an experimental class and VA SDN 27 Tapian Kandis as a class control. Sampling is done by simple random sampling technique. Research data was collected through pretest and posttest student learning outcomes. The hypothesis is proposed using the t test formula. The results showed that there was an effect of the Open Ended Approach and learning motivation on the mathematics learning outcomes of fifth grade elementary school students with the average student learning outcomes in the experimental class with 54.83 and posttest pretest 83.17 and the average learning outcomes for class students the control is 48.43 and posttest 76.05.